Eco-friendly electrochemical assay of oxytetracycline and flunixin in their veterinary injections and spiked milk samples - Yossra A. Trabik; Miriam F. Ayad; Amr M. Mahmoud; Hind A. Abdullatif; Adel M. Michael (BMC Chemistry, 2024)
Abstract Two solid-contact electrochemical sensors were developed for detection of each of oxytetracycline HCl (OXY), and the co-formulated non-steroidal anti-inflammatory drug flunixin meglumine (FLU) in veterinary formulations and animal-derived food products. The designed sensors were based on a glassy carbon electrode as the substrate material and high molecular weight polyvinyl chloride (PVC) polymeric ion-sensing membranes doped with multiwalled carbon nanotubes (MWCNTs) to improve the potential stability and minimize signal drift. For determination of OXY, the sensing membrane was modified with potassium tetrakis (4-chlorophenyl) borate (K-TCPB), which was employed as a cation exchanger, and 2-hydroxypropyl-β-cyclodextrin (HP-ßCD), which was used as an ionophore. A linear response within a concentration range of 1 × 10− 6-1 × 10− 2 M with a slope of 59.47 mV/decade over a pH range of 1–5 was recorded. For the first time, two potentiometric electrodes were developed for determination of FLU, where the sensing membrane was modified with tetra dodecyl ammonium chloride (TDDAC) as an anion exchanger. A linear response within a concentration range of 1 × 10− 5-1 × 10− 2 M and a slope of -58.21 mV/decade over a pH range of 6–11 was observed. The suggested sensors were utilized for the selective determination of each drug in pure powder form, in veterinary formulations, and in spiked milk samples, with mean recoveries ranging from 98.50 to 102.10, and without any observed interference. The results acquired by the proposed sensors were statistically analyzed and compared with those acquired by the official methods, and the results showed no significant difference. Graphical Abstract